Citizen’s Involvement in Local Development Activities in Nepal - Adhikari, Hari Prasad (Nepalese Journal of Management Research, 2022)
The main focus of this study is to investigate the extent of participation of the local people in local development activities in Nepal. Descriptive and analytical research design is used in this study. The data collected through questionnaire from 70 respondents was used for the analysis. As per the data collected, the findings showed that the marginalized people were not sharing equitable benefit from the local development activities including governmental services. Similarly, the extent of implementing local projects was found to be weak. The findings from this study can provide information about the citizen’s involvement in local development activities in Nepal. It could be helpful to provide some special guidelines to the policy makers for improving local governance.